Are networks important in order to secure a firm’s strategy? – A literature review - Córdova, Miguel (2017)
Since Granovetter´s (1973) research on weak and strong ties in relationship networks, a great amount of literature has been written about the network´s potential for firms in order to obtain more and different resources, reduce uncertainty from the environment, and finally secure its strategy. In this paper I present the strategy as a platform to build on with several key tools and resources, also as a real time development platform since it’s constantly influenced by networks. Networks are powerful indeed, and firms benefit from understanding its potential and capability to learn from it and mobilize it when it’s necessary. Networks not only influence the quantity and quality of resources that a firm can obtain, but, are also proficient in affecting the environment as well in order to facilitate the mobilization of these resources in the proper time.